Processing of Palm Midrib Waste into Animal Feed with a Fermentation Process that is integrated with a chopper in Sialang Village, Deli Serdang Regency - Susilawati; Rahayu, Siti Utari; Marponghatun; Suharman (ABDIMAS TALENTA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Sialang Village is one of the villages in North Sumatra, precisely located in Bangun Purba District, Deli Serdang Regency. The village is surrounded by oil palm plantations, both company-owned and private, with the main livelihood of the villagers working on oil palm plantations and also raising cattle. The village's potential to produce palm fronds waste is very large, but the villagers do not use palm fronds waste because they do not know how to treat this waste. Meanwhile, grass as animal feed has become increasingly difficult to obtain from time to time because residents have maximized the use of empty land for planting oil palm. Therefore, the University of North Sumatra community service team wants to apply science and technology in Sialang Village in the form of transfer of knowledge and technology on processing palm frond waste into animal feed integrated with chopper machines.